Chronic cutaneous and mucosal mucormycosis: Rhizopus arrhizus as a major pathogenic fungus - Xingyu Li; Chang Miao; Jinlei Yu; Fang Liu; Zhenlai Zhu; Jixin Gao; Dong Yan; Luming Hai; Gang Wang; Yubo Ma; Yanyang Guo; Meng Fu (Emerging Microbes and Infections)
Chronic cutaneous mucormycosis is a rare condition distinct from the acute form, characterized by a prolonged, indolent course and varied clinical presentations. This study presents a 5-year experience from a tertiary dermato-mycology clinic, identifying six cases, the majority of whom were immunocompetent, with trauma history reported in four patients. The median duration from symptom onset to diagnosis was 60 months. The primary pathogens identified were Rhizopus arrhizus, Mucor variabilis, and Lichtheimia ramosa. Histopathological analysis demonstrated the absence of fungal angioinvasion, a hallmark of acute mucormycosis, which likely accounts for the slower progression observed in chronic cases. Systemic Amphotericin B treatment achieved favourable outcomes in most patients though significant morbidity persisted in some cases. This case series underscores the clinical and pathological distinctions of chronic cutaneous mucormycosis, highlighting the potential influence of host factors and environmental conditions on chronicity. The predominance of Rhizopus arrhizus suggests that chronicity is driven more by hostpathogen interactions than fungal species-specific factors. Increased recognition of the atypical clinical features, such as diverse cutaneous manifestation and slower progression course, as well as the utilization of diagnostic tools including histopathology, fungal culture, and advanced molecular techniques, is essential for the timely diagnosis of this rare presentation.